Pengaruh skill abad 21 terhadap keputusan karir siswa sekolah menengah kerjuruan - Nikmarijal Nikmarijal; Janawi Janawi; Wahyudi Wahyudi; Komariah Komariah (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
By choosing SMK, it means that students have also chosen what profession they will pursue in the future. The process of choosing a future profession stretches over a long period of time and includes a variety of small choices that eventually lead to a particular professional path. To achieve the desired career in accordance with the demands of today's era, of course mastery of 21st century skills is needed. Because not all students who graduate from school are ready to work. This research is quantitative descriptive. The instrument used is a Career Choice Decision Making Questionnaire and a 21st Century Skill Ability Questionnaire. Based on Table 1 the significance value output above is known between 21st Century Skills (X) and Career Decisions (Y) the Significance value (Sig, (1-tailed) is .00 which means <0.05. So based on this it can be seen clearly that there is a significant correlation.